2014
DOI: 10.1038/nature12960
|View full text |Cite
|
Sign up to set email alerts
|

Derived immune and ancestral pigmentation alleles in a 7,000-year-old Mesolithic European

Abstract: Ancient genomic sequences have started revealing the origin and the demographic impact of Neolithic farmers spreading into Europe1–3. The adoption of farming, stock breeding and sedentary societies during the Neolithic may have resulted in adaptive changes in genes associated with immunity and diet4. However, the limited data available from earlier hunter-gatherers precludes an understanding of the selective processes associated with this crucial transition to agriculture in recent human evolution. By sequenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
301
1
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 340 publications
(328 citation statements)
references
References 29 publications
23
301
1
3
Order By: Relevance
“…This latter finding was unexpected given the archaeological evidence of a long-term occupation of Neanderthals in [47,48]. High-coverage genomes of Late Pleistocene Europeans-and also from other populations-will be needed to estimate accurately if other admixture events could have occured with Neanderthals or Denisovans.…”
Section: High-coverage Genomesmentioning
confidence: 87%
“…This latter finding was unexpected given the archaeological evidence of a long-term occupation of Neanderthals in [47,48]. High-coverage genomes of Late Pleistocene Europeans-and also from other populations-will be needed to estimate accurately if other admixture events could have occured with Neanderthals or Denisovans.…”
Section: High-coverage Genomesmentioning
confidence: 87%
“…This high similarity of modern Basques to El Portalón individuals was surprising because Basques have been posited as a remnant isolated population with a close relationship to the Mesolithic inhabitants of the region, based on classical genetic markers (26) and mtDNA haplogroup data (8), although the level of continuity has been unclear (12,13). The Basque language (Euskara) is a linguistic isolate, with no proven relationships with any languages now spoken in Europe or elsewhere (11), and it has commonly been concluded that the Basque language is a relict of the ancient, preagricultural linguistic diversity of Europe, with roots as far back as the Paleolithic (SI Appendix, section S12) (9).…”
Section: Resultsmentioning
confidence: 99%
“…The relationship of early Iberian farmers to their Central European counterparts and HG groups in Iberia, as well as their contribution to the present-day genomic variation in Iberia, is crucial to understanding the demographic history of the region. Of particular interest is the connection of Basques to different ancient groups in Iberia, to shed light on their long-debated origins (6)(7)(8)(9)(10)(11)(12)(13).…”
mentioning
confidence: 99%
“…I2a has indeed been found in Mesolithic and Neolithic Central and North European hunter-gatherers [33,34,40,41], as well as in Neolithic remains of southwestern Europe [44,45]. Haplogroup I2a (and possibly I1) might represent a pre-farming legacy of the NRY variation in Europe, alongside the recently described pre-Neolithic C (M130) haplogroups in Russia and Spain [35,42]. Y chromosome haplogroups from STA and LBKT samples, such as haplogroups G2a2b and F*, have also been reported from the Central European LBK [38], and support a homogeneity of paternal lineages among early farmers.…”
Section: Discussionmentioning
confidence: 99%
“…Ancient genomic studies have described the early farmers as genetically most similar to extant populations of southern Europe [31,33,40,41]. Y chromosome data from prehistoric Europeans is still scarce but relevant for our study (electronic supplementary material, dataset S20), including hunter-gatherers [33][34][35]40,42], and early farmers from Germany [38,40], eastern Hungary [41], Austria [43] and southwest Europe [40,44,45].…”
Section: Introductionmentioning
confidence: 99%